Monads on Segre varieties - Macias Marques, Pedro (2013)
We construct a family of monads on the Segre variety of type 0 --> O_{P^l× P^m}(-1,-1)^a --> O_{P^l× P^m}^b --> O_{P^l× P^m}(1,1)^c --> 0 and give a cohomological characterisation of torsion free sheaves that are the cohomology of these monads.